PERTUMBUHAN DAN LAJU PENANGKAPAN IKAN TONGKOL KOMO (Euthynnus affinis Cantor 1849) YANG DIDARATKAN DI PELABUHAN PERIKANAN SAMUDERA BELAWAN SUMATERA UTARA Growth and the Rate of Catch of Eastern Little Tuna (Euthynnus affinis Cantor 1849) Landed on Belawan - Febrina Rahmadanti Putri; Darma Bakti; Desrita Desrita (AQUACOASTMARINE, 2015)
Eastern Little Tuna is one of the fisheries commodity that has high economic value in Medan.This type of fish is the most demand in the local market, thus it becomes the main target forfisherman to catch. However, this activity has negative impact for the population of EasternLittle Tuna. This study was done at KUD Gabion on November 2014 until April 2015. Thisresearch aims to study about the growth pattern, factor condition of plumpness, and also therate of exploitation in order to determine management model for the fish resource. Theprimary data is the total length and weight of 371 samples of Eastern Little Tuna, while thesecondary data is the temperature of sea surface. The cohort length of fish is separated byBhattacarya method in FISAT II software. The Von Bertalanffy growth parameters estimatedwere asymtotic length (L∞) = 628,95 mm, growth coefficient (K) = 0,24 year-1 and the age atzero length (t0) = -0,30 from Pauly’s empirical equation. Then, the growth equation forEastern Little Tuna is Lt = 628.95 (1‐e[-0.24(t+0,30)]), whereas value of b obtained from relationsof lenght – weight Eastern Little Tuna is 2,963. A growth pattern of Eastern Little Tuna isnegative allometric with an equation growth W=0,00002L2,963. The highest and the lowestvalue of factor condition are 0,40 and 2,11. The rate of total mortality (Z) Eastern Little Tunais 2,097 year-1 with natural mortality rate (M) 0,30 year-1 and fishing mortality rate (F) 1,79year-1 thus the rate of exploitation is obtained with the amount 0,85 and the value of thisexploitation rate has exceeded the value of the optimum exploitation, which is 0,5.Keywords: Eastern Little Tuna, Growth, Mortality, Malacca Strait